Age discrimination in acute care hospital settings?: focus on verbal care interactions with cognitively impaired older patients - Schnabel, Eva-Luisa (2021)
Objective: Acute care hospital settings represent a challenging environment for vulnerable older patients such as those with dementia. In particular, ageist behavior as reflected in so-called elderspeak communication has been considered as a crucial factor contributing to neuropsychiatric symptoms, suboptimal medical decision making, and poorer treatment outcomes in patients with dementia. Despite its linkage with negative health outcomes, the bulk of previous research on elderspeak has been conducted in nursing home settings and did not simultaneously consider multiple contextual conditions. Following a contextually-driven framework, the present dissertation concentrated on everyday care interactions between older patients and nurses (micro-level) in two German acute hospital settings differing in patient characteristics and geriatric expertise (macro-level). Paper 1 focused on the communication behavior of cognitively impaired (CI) versus cognitively unimpaired (CU) older inpatients. Paper 2 investigated nurses’ emotional tone toward older inpatients with a particular focus on the role of the acute hospital setting and patients’ cognitive impairment. Paper 3 examined the role of proximal (cognitive and functional impairment) and distal contextual factors (acute hospital setting, psychogeriatric knowledge, and evaluative age stereotypes) in predicting the occurrence of elderspeak. Method: Data of all three papers were based on a cross-sectional study focusing on elderspeak in an acute internal medicine ward (n = 36 beds, mean length of stay = 4.9 days) and an acute geriatric ward (n = 35 beds; mean length of stay = 16.5 days). A total of 106 older patients participated in the study. Patients were between 66 and 96 years old (M ± SD Years = 83.08 ± 6.19). Half of the patients (49%) were severely cognitively impaired (M ± SD 6CIT = 10.80 ± 8.60) and 56% were female. In total, 34 registered nurses took part in the study. Nurses were between 22 and 59 years old (M ± SD Years = 38.93 ± 12.30). The majority of nurses were female (79%). Based on a mixed methods design, three types of data sources were used: (a) audio-recordings during the morning (49%) or evening care (51%), (b) patient data from the medical information system, and (c) standardized interviews with patients and nurses. The first paper was based on a psychometric study validating a tool to assess communication behavior in dementia (CODEM) for use in CI patients in the acute care hospital setting. Patients were observed by trained research assistants during a standardized interview situation and rated afterward. In the second paper, an emotional tone rating procedure was performed to differentiate between a person-centered and a controlling tone of nurses’ voice toward older inpatients (Cronbach’s α = .98 for both subscales). A total number of 92 audio-recorded clips were evaluated by 12 naïve raters (M ± SD Age = 32.75 ± 9.33 years) based on their impressions of nurses’ vocal qualities. The third paper was driven by psycholinguistic analysis using manual coding (κ = .85–.97) and computer-assisted procedures for extracting likely harmful (diminutives, collective pronoun substitutions, tag questions) and hybrid features of elderspeak (sentence fragments, mean length of utterances, speech rate, type-token ratio, complex units). Results: The first paper demonstrated that CODEM is a reliable and valid tool to examine the communication behavior of CI patients in the acute care hospital setting. CI patients significantly differed from CU patients in terms of an overall lower frequency of communication behavior as well as a higher occurrence of nonverbal when compared to verbal communication behavior. The second paper revealed that the emotional tone of nurses’ voice toward older patients was perceived as largely person-centered and not so much as control-centered. Finally, the third paper provided further evidence on the existence of likely harmful diminutives (61%), collective pronouns substitutions (70%), and tag questions (97%). An important finding of Paper 2 and 3 was that functional impairment more strongly contributed to controlling tones of nurses’ voice and elderspeak than cognitive impairment and acute hospital setting. Whereas a low percentage of older patients reported perceived age discrimination (2%), more than one third of older patients (36%) endorsed at least one type of ageist event during their hospital stay. Overall, nurses’ views on aging were largely negative. Conclusions: A large interindividual variability of communication resources and deficits has been demonstrated in acutely ill older inpatients. Furthermore, key features of elderspeak have been identified at the verbal and nonverbal communication level. Taken together, the present dissertation provides initial evidence for the occurrence of ageism and elderspeak in acute care hospital settings. Furthermore, it extends previous elderspeak research by discovering the dominant role of functional impairment that may be more strongly involved in the process of negative stereotype activation than cognitive impairment. The present work also provides a unique, multi-level, and interdisciplinary measurement approach for examining ageism in naturally occurring interactions. Such an ecologically valid approach may inform future studies and help to systematically combat ageism in high-risk groups. Finally, the current outbreak of ageism underpins that evidence-based interventions are urgently needed to overcome ageism and to establish a new narrative on aging in the public discourse.